Predileksi yang Disukai Oleh Tungau Pada Kambing Kacang Lokal - Mufti Kamaruddin; M. Hanafiah; Yudha Fahrimal; Winaruddin Winaruddin (Agricultural Faculty, 2001)
ABTSRACT. This rescerch was done in second stage, The first one of study was done in field at Darul Imarah contry Aceh Besar. Examined of ample in Parasitology Laboratory of Syiah Kuala University. This aimed of the research to know how predilected on infested of mite in the host. This study used 50 goats were the clinically infected the each of sample pick up erupted of skin in the area of face, ear, neck, beck, fore legs and wrist. Paramaeter of the research were species and each area of host. The result showed that location has a significant effect on mites infestation. The largest number of Sarcopies are found on the face area and the smallest number in the hindd legs. On the other hand, the largest number Chorioptes and Psoroptes are found in the hind legs and samallest in the face and ear area.Key Word :Sarcoptes; Chorioptes and Psoroptes